2009
DOI: 10.1016/j.trstmh.2008.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Association between nutritional status, environmental and socio-economic factors and Giardia lamblia infections among children aged 6–71 months in Brazil

Abstract: A cross-sectional study was conducted on a randomised sample of 405 children aged 6-71 months in Brazil to investigate the association between nutritional status, environmental and socio-economic factors and Giardialamblia infection. Data collection entailed an interview, anthropometric measurements and the collection of faeces and venous blood samples. The analysis was performed using multivariate logistic regression. The prevalence rate for G. lamblia was 26.3%. Nutritional status evaluation showed that 7.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
2
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 16 publications
9
37
2
12
Order By: Relevance
“…1 Most studies of this parasite have found that young children are the most infected, but no correlation between giardiasis and age was found in this investigation. This finding does not corroborate the results reported by Quihui et al 14 and Ostan et al, 15 who found a correlation.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…1 Most studies of this parasite have found that young children are the most infected, but no correlation between giardiasis and age was found in this investigation. This finding does not corroborate the results reported by Quihui et al 14 and Ostan et al, 15 who found a correlation.…”
Section: Discussioncontrasting
confidence: 70%
“…Giardia duodenalis is the most frequent protozoon among the endoparasites, with prevalence rates of 23-30% in developing countries and of 2-5% in industrialized countries. 1 Giardia duodenalis (synonyms: G. lamblia, G. intestinalis) is a common endoparasite in humans and in domestic and wild animals throughout the world, 2 infesting the small intestines of young individuals, especially in their early years. Most infections are asymptomatic and, when present, symptoms vary from diarrhea to abdominal pain to poor intestinal absorption, and the infection is responsible for retarding the growth and development of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, because the frequency of exclusively breastfed children was low in our study population (personal observation), we did not include it in our analysis. In Peru, children more than two years of age were more likely to be infected with protozoans, 53 whereas no relationship was detected between age and persistent Giardia spp. infections (lasting !…”
Section: Discussionmentioning
confidence: 96%
“…For instance, the anthropometric parameter HAZ has been shown to be markedly negatively influenced by giardiasis in the Amazon region of Brazil [10]. G. intestinalis infection was also observed to influence nutritional status in northeastern Brazil [31][32][33]. In Rwanda, G. intestinalis infection was identified as a predictor of being underweight and severe malnutrition [30].…”
Section: Discussionmentioning
confidence: 99%